Regional Event Tourism Funding Policies: A Strategic-Relational Critique of Current Practice. (April 2021) - Ormerod, Neil; Wood, Emma H.
Taking a strategic-relational approach we critique a range of event tourism funding policies and practices that seek to create regional and/or national event strategies. A multiple case study method combining document analysis and key informant interviews within selected regions provides insights into the political nature of event funding, the equity of its distribution, and the decision processes involved. Programs were found to operate in a sensitive and complex context due to intertwined power relationships between policy and agency embedded within governments. We conclude that to bring about broader benefits and legacies a paradigm shift is needed to rebalance economic and social outcomes within funder objectives and governance structures. This needs to include innovation in evaluation and wider more meaningful stakeholder engagement. The study shows that without fundamental change in policy, national and regional funding programs are likely to continue to operate within their existing narrow remit.